Food protein‐induced enterocolitis syndrome. Issue 9 (29th August 2019) - Caubet, Jean‐Christoph; Cianferoni, Antonella; Groetch, Marion; Nowak‐Wegrzyn, Anna
Abstract: Food protein‐induced enterocolitis syndrome (FPIES) is a non‐IgE‐mediated gastrointestinal food allergic disorder that has gained a major interest the past decade. FPIES prevalence, which still needs to be accurately determine in different populations, appears to be higher than previously thought (ie up to 0.7% in infants in the 1st year of life). FPIES to seafood in adults is also increasingly reported; limited data suggest that adult FPIES is most commonly triggered by shellfish, tends to affect females more than men, is characterized by a significant delay in diagnosis and a prolonged course. The first international consensus guidelines on diagnosis and management of FPIES have been published in 2017, proposing new diagnostic criteria as well as new criteria for a positive oral food challenge. However, there is a need to develop new biomarkers to improve the diagnosis and management of FPIES patients, and this requires a better understanding of the pathophysiology. Recently, the role of T cells has been questioned and a major role of innate immune cells has been suggested in acute FPIES. Regarding the treatment of acute FPIES reaction, ondansetron has emerged as an adjunct to intravenous rehydration in moderate‐severe reactions and as a first‐line treatment in mild reactions. Important information regarding the nutritional management of FPIES patients that might be complex has also been provided in the international guidelines. In this review, we discuss recent advances regarding all those different aspects.